2019
DOI: 10.1007/978-3-030-36683-4_35
|View full text |Cite
|
Sign up to set email alerts
|

Describing Alt-Right Communities and Their Discourse on Twitter During the 2018 US Mid-term Elections

Abstract: The alt-right is a far-right movement that has uniquely developed on social media, before becoming prominent in the 2016 United States presidential elections. However, very little research exists about their discourse and organization online. This study aimed to analyze how a sample of alt-right supporters organized themselves in the week before and after the 2018 midterm elections in the US, along with which topics they most frequently discussed. Using community finding and topic extraction algorithms, result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Furthermore, research on the Alt-Right in Europe found that members are often distrustful of traditional media and rely on social media as their primary news source [123]. The central topics of this social media discourse include those social issues found here to be mitigated by trust in conservative media: discrimination against Whites, Islamic terrorism, government corruption, and climate change [117,119]. The mitigating effect of lower trust in conservative media may be explained by the Alt-Right's reliance on this online media environment rather than traditional conservative news sources, wherein specific social issues are emphasized resulting in the interaction effects observed here.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Furthermore, research on the Alt-Right in Europe found that members are often distrustful of traditional media and rely on social media as their primary news source [123]. The central topics of this social media discourse include those social issues found here to be mitigated by trust in conservative media: discrimination against Whites, Islamic terrorism, government corruption, and climate change [117,119]. The mitigating effect of lower trust in conservative media may be explained by the Alt-Right's reliance on this online media environment rather than traditional conservative news sources, wherein specific social issues are emphasized resulting in the interaction effects observed here.…”
Section: Discussionmentioning
confidence: 95%
“…The US has a particularly large and active right-wing digital news infrastructure, which has been associated with increasing distrust in traditional news media [114,115]. Within this broader architecture, the Alt-Right has an expansive online media environment encompassing a variety of platforms and content creators, including dedicated Alt-Right news sites, blogs, podcasts, YouTube videos, memes, and social media [115][116][117][118][119][120][121]. Furthermore, Alt-Right adjacent communities on YouTube, the Alt-Light, and Intellectual Dark Web, have served as entry points to the more extremist content of the movement [120,122].…”
Section: Discussionmentioning
confidence: 99%
“…It is distributed under the terms of the Creative Commons Attribution 4.0 (CC BY) License which permits use, distribution and reproduction in any medium, provided the original work is properly cited. populist and far-right movements all over the world, 1,2 the socio-political context has experienced a change that has deeply a®ected the society. Both the political discourse and citizen worries have also changed.…”
Section: Introductionmentioning
confidence: 99%
“…There are several problems that are studied in this topic. The most popular are: hate speech detection, [8][9][10] political polarization, 1,11,12 community¯nding problems, [13][14][15] information di®usion, 16,17 or the study of how people in°uence each other through their posts on the OSN. 1,18 Noticing this issue, the European Union has founded several programs and projects to address radicalization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation